Insecticide selectivity to the parasitic mite Acarophenax lacunatus (Cross & Krantz) (Prostigmata: Acarophenacidae) on Rhyzopertha dominica (Fabr.) (Coleoptera: Bostrichidae) - Gonçalves,José R. (2004)
The presence of natural enemies in stored grains and the need of pest control alternatives led to the assessment of the effect of insecticides on the mite species Acarophenax lacunatus (Cross & Krantz), an egg parasite of the stored grain pest Rhyzopertha dominica (Fabr.). The insecticides bifenthrin, deltamethrin, pirimiphos-methyl and fenitrothion were tested at 0.4, 0.5, 0.8 and 10 ppm, respectively. Insecticide treated wheat grains were spread in petri dishes and infested with 25 adults of R. dominica. Seven days later, three mites were added to each dish, in four replicates. The number of adults of R. dominica, grain weight loss and instantaneous rate of increase (r i) of A. lacunatus were lower when the grain was treated with deltamethrin. Bifenthrin, fenitrothion, and pirimiphos-methyl were less effective in controlling the pest, but they were selective in favor of the mite, showed higher number of physogastric females and r i of A. lacunatus. Therefore, deltamethrin was less selective in favor of the mite species. Nonetheless the parasitic mite was able to parasitize eggs of R. dominica on wheat treated with all the insecticides evaluated.